Ответы и объяснения

2013-10-04T14:11:33+04:00
92) 7a*3/12*b=7a/4b
93) -11p^3*12q^2/8q^4*55p= -p^2*3/2*q^2*5=-3*p^2/10q^2
94)  x^{n+1} * y^{n+1} / y^{n-1} *  x^{n+3} = y^{2}/x^{2}
95) 5(x+y)*4x^2/8xy*7(x+y)=5*x/2*y*7=5x/14y
96) (a-x)^2*(2a^2+4ax+2x^2)/(a+x)^2*(3a^2-6ax+3x^2)=2 *(a-x)^2*(a^2+ax+x^2)/3*  (a+x)^2*(a^2-2ax+x^2)=2*(a-x)^2 *(a+x)^2 /3 (a+x)^2 *(a-x)^2  =2/3
97)( (a^2+6ab+9b^2)/(a^2+10ab+25b^2)  )^2=1/16
( (a+3b)^2/(a+5b)^2 )^2=1/16     по условию а=-b  (   (2b)^2/(4b)^2  )=1/16
( 4b^2/16b^2  )^2=(1/4)^2=1/16
98) (y^2-16)*(xy+y^2)/(x^2+xy)*(4y-y^2)*(y^2+y-12)=(y-4)*(y+4)*y(x+y)/x(x+y)*(y+4)*(y-3)=(y-4)*y/(y-3)*x
99) (a^2+3ab-2a-6b)*(a-3b)/(a^2-9b^2)*(a^2-4)=(a(a+3b)-2(a+3b))*(a-3b)/(a+3b)*(a-3b)*(a-2)*(a+2)=(a-2)(a+3b)/(a+3b)*(a-2)*(a+2)=1/(a+2)
100)(x/2y)^3=x^3/8y^3
101) ((x-y)/(x+y))^3*((x-y)^2+4xy)/ ((x+y)^2-4xy)=  ((x-y)/(x+y))^3/(x^2+y^2+2xy)/(x^2+y^2-2xy)=(x-y)^3*(x+y)^2/(x+y)^3*(x-y)^2=(x-y)/(x+y)